Learning to think for the development of environmental ethics model for mangrove children - Jinarak, Jitikan; Ounvichit, Tassanee (Kasetsart Journal of Social Sciences, 2021)
Inculcation of ethics heavily influenced by materialism may fail to arrest environmental problems. Leveraging on the thinking potential of children in their real life context, this action research was carried out with 15 children from Ko Klang mangrove community in Krabi province with the purposes to analyze their thinking patterns and innovate an alternative model for environmental ethics development. The verbalized data on their invisible thinking were collected by interviewing them as well as their teachers and parents and participant observation. The data were analyzed and coded against a schedule of 29 thinking modes and compared with the results of the test conducted to identify any trends of change in their egocentric, homocentric and ecocentric ethics. The results of the study indicated that there was a positive influence of the diversity and thoroughness of the thinking patterns for the development of ecocentric ethics, which was characterized by three main aspects of thinking about environmental situations, thinking about solving environmental problems, and thinking with environmental goals in mind. The Learn to Think for the Development of Environmental Ethics Model was innovated, comprising four steps of building confidence in self, reflecting on the value and attitudes towards the mangrove environment, planning environmental actions in the mangrove community, and reflecting on a new environmental ethical self. Recommended for further study were the sustainability of the children’s environmental ethics and the capacity development of learning managers with regard to uses of questions to stimulate thinking for environmental ethics development.